Reliable Change in Postconcussive Symptoms and Its Functional Consequences Among Children With Mild Traumatic Brain Injury - Yeates, Keith Owen (2012)
OBJECTIVE: To examine reliable change in postconcussive symptoms and its functional consequences among children with mild traumatic brain injury (TBI) over the first year postinjury as compared with children with orthopedic injuries. DESIGN: Prospective, longitudinal cohort. SETTING: Emergency departments at 2 children’s hospitals. PARTICIPANTS: Eight- to 15-year-old children with mild TBI (n = 186) or orthopedic injuries (n = 99). MAIN EXPOSURE: Closed-head or orthopedic trauma. MAIN OUTCOME MEASURES: Parents rated preinjury symptoms retrospectively shortly after injury and post-concussive symptoms at 2 weeks and 3 and 12 months postinjury. A regression-based approach was used to determine whether each child displayed reliable increases in postconcussive symptoms at each postinjury occasion. Health-related quality of life was assessed at 3 and 12 months postinjury. Information regarding children’s educational programming was collected at the initial and 12-month assessments. RESULTS: Children with mild TBI were significantly more likely than those with orthopedic injuries to show reliable increases in both cognitive and somatic symptoms. Group differences in the likelihood of reliable increases became less common with time for somatic symptoms but persisted to 12 months postinjury for cognitive symptoms. Among children with mild TBI, reliable increases in symptoms were more common among children with loss of consciousness or abnormalities on neuroimaging. Reliable increases in symptoms were associated with significant declines in health-related quality of life and an increased likelihood of educational intervention. CONCLUSION: Many children with mild TBI show reliable increases in postconcussive symptoms that are associated with significant functional impairment in their daily lives.